Towards Dynamic Policy for Early Childhood Development Enhanced the Growth of Self-Regulations - Md. Rahimullah, Miah; Mohamed Sharif, Bin Mustaffa; Surena, Binti Sabil; Amalia, Binti Madihie; Jamayah, Binti Saili; Kiew Sayok, Alexander (Science Publishing Corporation Inc, 2018)
Dynamic education policy and value system can change only with growth and development. This education plays a key role in enhancing about these changes, and the right time to initiate this process of education is better from early childhood. The study explores the issues and challenges of doing early childhood development (ECD) policy for growth of self-regulations along with Sarawakian Primary Schools in Malaysia. Recently the problems of early childhood providing primary schools at Bau district have been starling due to lack of instruments for pre-school services. These issues are now then become more tangled because of its multiracial education policy integration with students’ self-regulations from cultural diversity conditions belonging to variety beliefs and attitudes. Quantitative and qualitative related data were obtained through field observation, interviews and field surveys while secondary data collected from diverse sources. Nearly 57% of the respondents agreed for improvement of ECD policy with sustainable mechanism of monitoring and implementation at each of developmental stages of child. The research has also shown that there are gaps between the aspired and implemented comprehensive education policies for more quality preschool classes and initiatives. The study suggests future research trajectories of a new collaborative alternative dynamic approach to drive the methodological agenda and recommendations on ways to further incorporate the demanding ECD policy instruments towards growth of self-regulations.